Peran Pendidikan Politik GMPI dalam Peningkatan Kualitas Kader Partai Persatuan Pembangunan Periode 2021-2026 - Ilzam Thoriq Robbany; Lusi Andriyani (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
Generasi Muda Pembangunan Indonesia (GMPI) is a youth organization that functions as a party wing organization and plays a strategic role in providing political education for the cadres of the United Development Party (PPP). Political education is essential to improve cadre quality in terms of ideological knowledge, organizational capacity, and readiness to participate in political activities. This study aims to analyze the role of GMPI in political education, examine the institutional relationship between GMPI and PPP, and identify the challenges and obstacles faced in its implementation. This research employs a qualitative approach using primary and secondary data sources. Data were collected through interviews, observations, and documentation. Data analysis was conducted qualitatively through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that GMPI actively conducts political education through cadre development programs, guidance activities, and capacity building. The political education implemented by GMPI has a positive impact on improving the quality of PPP cadres, particularly in political understanding, discipline, and participation in party activities. However, GMPI still encounters several constraints, including limited resources, program consistency issues, and internal organizational dynamics. These findings highlight the importance of strengthening the role of youth organizations as sustainable instruments of political education. The implications of this study encourage political parties to enhance youth cadre development synergy in order to produce qualified, competent, and sustainable political cadres.